1993
DOI: 10.1203/00006450-199309000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Neutrophils and Eosinophils Express Normal Levels of L-Selectin

Abstract: ABSTRACT. L-selectin is a leukocyte adhesion molecule important in the initial stages of the interaction of neutrophils with endothelium during neutrophil emigration from the bloodstream. Neutrophils and eosinophils from newborn infants express significantly less L-selectin than do neutrophils and eosinophils from adults. It is not known whether I.-selectin expression on fetal granulocytes is similarly decreased. We studied fetal blood specimens obtained for a variety of clinical indications by percutaneous um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 16 publications
0
18
1
Order By: Relevance
“…Smith et al (23) reported that neutrophils from human preterm fetuses have expression of L-selectin similar to that of the adult. This would suggest that the developing infant is capable of producing L-selectin on the surface of its neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al (23) reported that neutrophils from human preterm fetuses have expression of L-selectin similar to that of the adult. This would suggest that the developing infant is capable of producing L-selectin on the surface of its neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, cells were incubated for 20 min at 4°C in the dark with MAbs against CD14, IL-6, IL-8, and tumor necrosis factor-␣ (TNF-␣; Pharmingen, Heidelberg, Germany). Preincubation with an excess of unlabeled anticytokine MAbs for 20 min at 4°C in the dark served as a negative control for intracellular staining to each sample (21). Monocytes were gated by means of their CD14 positivity, and number of cytokine-positive cells as well as the MFI were measured of a minimum of 2000 cells per sample.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, little is known to date about the phagocytic and oxidative capacity as well as the adhesion molecule expression of fetal neutrophils and monocytes. The expression of several adhesion molecules essentially involved in migration was reported to be significantly impaired in neonates and to contribute to the impaired neonatal immune response (18 -20); however, only very limited data are available for fetuses (21). Similarly, to our knowledge, there are no reports on the ability of fetal monocytes to produce proinflammatory cytokines in response to endotoxin challenge.…”
mentioning
confidence: 99%
“…A niunber of abnormalities have been described in the host defence mechanisms of the newborn infant, including neutrophil function. Studies of fetal and neonatal neutrophils (both term and premature) have consistently documented diminished chemotaxis [9][10][11][12][13] and adherence [14][15][16], deficiencies in the expression of adhesion molecules and complement receptors [17][18][19][20][21][22].…”
Section: C) 1995 Blackwell Sciencementioning
confidence: 99%
“…While Smith & Tabsh found that resting and stimulated fetal neutrophils express normal adult levels of L-selectin [21], Koenig et ai have suggested that there is less L-selectin loss from stimulated fetal cells [23]. The neutrophil expression of CDIla/CDI8 on term infant cells has been found to be no different from that on adult neutrophils [18].…”
Section: C) 1995 Blackwell Sciencementioning
confidence: 99%